Morbidity pattern amongst elderly patients presenting at a primary care clinic in Nigeria - Lawrence A. Adebusoye; Modupe M. Ladipo; Eme T. Owoaje; Adetola M. Ogunbode (AOSIS, 2011)
Background: The elderly comprise the fastest-expanding age group globally, with the greatest increase occurring in developing countries. Disease and deteriorating health are implicitly assumed to be associated with ageing, as chronic medical illnesses mostly present with increasing age. Objectives: To describe the morbidity pattern of elderly patients presenting at the General Outpatients Clinic of the University College Hospital, Ibadan, Nigeria. Method: This was a cross-sectional descriptive study of 500 elderly respondents who presented at the clinic between September 2004 and April 2005. They were interviewed according to the format of the electronic, second revision of the International Classification of Primary Care (ICPC-2-E) questionnaire. Main outcome measurements were the prevalence of various morbidities, self-reported health status and socio-demographic characteristics. Body mass index (BMI) was used to assess respondents' nutritional status. Results: Respondents were found to under-report their actual health problems. The mean ± s.d of self-reported health problems was 1.7 ± 0.9 (range 1-6), while the mean ± s.d of diagnosed morbidities was 2.7 ± 1.4 (range 1-8). The most prevalent morbidities were hypertension(40.0%), cataracts (39.4%) and osteoarthritis (26.8%). The prevalence of anaemia was 8.0% (females = 11.2%; males = 2.6%), and it was significantly associated with gender (p = 0.001). Nutritional status indicated a high prevalence of overweight and obesity (51.8%), which was significantly higher amongst the female respondents than the males (p = 0.001). Conclusion: The prevalence of chronic medical illnesses was high amongst the elderly in this setting. In addition, the elderly under-reported their actual health problems. The high prevalence of overweight and obesity amongst the elderly in this setting calls for public health action that advocates lifestyle changes to manage the health of the elderly.